A NEW ROBUST ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF RIBOCICLIB AND LETROZOLE IN SOLID DOSAGE FORM (TABLET) - SATAPATHY, BHAGYALATA; BANGARI, CHAITANYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to develop a new robust, sensitive, precise, accurate RP-HPLC analytical method and validate for simultaneous estimation of ribociclib and letrozole in solid dosage form (tablet). Methods: The chromatographic separation was carried out on Waters, symmetry C18 (150 mm×4.6 mm with 3.5 μm), mobile phase used was a mixture of buffer and acetonitrile in the ratio of 80:20, with flow rate of 1ml/min and injection volume of 10 μL for the assay. The detection was done using PDA at 260 nm, with run time of 5 min. The retention time for the drugs ribociclib and letrozole was detected to be 2.648 min and 3.151 min, respectively. The method was validated according to ICH guidelines. Results: The linearity of letrozole and ribociclib was observed to be in the range of 0.50–7.50 and 40.01–600.15, Correlation coefficient (r2) 0.999 and 0.9983, respectively. Accuracy for ribociclib and letrozole is carried out by repeatable concentrations of 50%, 100%, and 150. Validation factors of robustness and ruggedness were detected to be in limits. Conclusion: The developed method was simple, rapid, and consistent; it can be used for the simultaneous estimation of ribociclib and letrozole tablet dosage form in routine analysis.